ANALISIS KESALAHAN PADA PENGGUNAAN KONJUNGSI KOORDINAT OLEH SISWA KELAS XI SMA N 3 MANADO - Dolonseda, Marcelyn Maya Liza (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This article, entitled ?Error Analysis of the use of Coordinating Conjunction By Grade XI Students at SMA N 3 Manado?, is an attempt to analyze and classify errors in the use of coordinating conjunction. It was carried out at SMA N 3 Manado. The method used in this research is descriptive. Ellis?s (1998) theory is used to explain the types of errors. This theory is intended to find out the errors made by the students. The data of the research were collected using a  4-part-test form. Part 1 is multiple choice, part 2 is filling  in the blank, part 3 is determining true or false sentences, and part 4 is unscrambling sentences into correct. The results of this research show that the students? score of errors in the use of coordinating conjunction and is higher than but, or, and for. The use of coordinating conjunction for has the lower percentage. In terms of the types of errors made by students the higher percentage is misinformation, then misordering and the lower percentage is omission. Based on the results, it can be concluded that students are still confused on how to put the right coordinating conjunction on the sentence. So, they made these kinds of errors such as omission, misinformation and misordering. Keyword : Error analysis, coordinating conjunction,high school students, omission, misinformation, misordering.